let L be 1-sorted ; :: thesis: for A, B, C being AlgebraStr over L st A is Subalgebra of B & B is Subalgebra of C holds
A is Subalgebra of C

let A, B, C be AlgebraStr over L; :: thesis: ( A is Subalgebra of B & B is Subalgebra of C implies A is Subalgebra of C )
assume that
A1: A is Subalgebra of B and
A2: B is Subalgebra of C ; :: thesis: A is Subalgebra of C
A3: the carrier of A c= the carrier of B by ;
then A4: [: the carrier of A, the carrier of A:] c= [: the carrier of B, the carrier of B:] by ZFMISC_1:96;
the carrier of B c= the carrier of C by ;
hence the carrier of A c= the carrier of C by A3; :: according to POLYALG1:def 3 :: thesis: ( 1. A = 1. C & 0. A = 0. C & the addF of A = the addF of C || the carrier of A & the multF of A = the multF of C || the carrier of A & the lmult of A = the lmult of C | [: the carrier of L, the carrier of A:] )
thus 1. A = 1. B by
.= 1. C by ; :: thesis: ( 0. A = 0. C & the addF of A = the addF of C || the carrier of A & the multF of A = the multF of C || the carrier of A & the lmult of A = the lmult of C | [: the carrier of L, the carrier of A:] )
thus 0. A = 0. B by
.= 0. C by ; :: thesis: ( the addF of A = the addF of C || the carrier of A & the multF of A = the multF of C || the carrier of A & the lmult of A = the lmult of C | [: the carrier of L, the carrier of A:] )
thus the addF of A = the addF of B || the carrier of A by
.= ( the addF of C || the carrier of B) || the carrier of A by
.= the addF of C || the carrier of A by ; :: thesis: ( the multF of A = the multF of C || the carrier of A & the lmult of A = the lmult of C | [: the carrier of L, the carrier of A:] )
thus the multF of A = the multF of B || the carrier of A by
.= ( the multF of C || the carrier of B) || the carrier of A by
.= the multF of C || the carrier of A by ; :: thesis: the lmult of A = the lmult of C | [: the carrier of L, the carrier of A:]
A5: [: the carrier of L, the carrier of A:] c= [: the carrier of L, the carrier of B:] by ;
thus the lmult of A = the lmult of B | [: the carrier of L, the carrier of A:] by
.= ( the lmult of C | [: the carrier of L, the carrier of B:]) | [: the carrier of L, the carrier of A:] by
.= the lmult of C | [: the carrier of L, the carrier of A:] by ; :: thesis: verum